2018
DOI: 10.1186/s13075-018-1564-5
|View full text |Cite
|
Sign up to set email alerts
|

Osteoclasts degrade bone and cartilage knee joint compartments through different resorption processes

Abstract: BackgroundOsteoclasts have been strongly implicated in osteoarthritic cartilage degradation, at least indirectly via bone resorption, and have been shown to degrade cartilage in vitro. The osteoclast resorption processes required to degrade subchondral bone and cartilage—the remodeling of which is important in the osteoarthritic disease process—have not been previously described, although cathepsin K has been indicated to participate. In this study we profile osteoclast-mediated degradation of bovine knee join… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 61 publications
(75 reference statements)
2
44
0
1
Order By: Relevance
“…Osteoclastogenesis is a prerequisite for osteochondral remodeling, and the osteoclast resorption process is required to degrade subchondral bone and cartilage [ 50 ]. Our study found a significant increase in osteoclasts in the subchondral bone and cartilaginous endplate of the OVX group, consistent with the previous findings.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoclastogenesis is a prerequisite for osteochondral remodeling, and the osteoclast resorption process is required to degrade subchondral bone and cartilage [ 50 ]. Our study found a significant increase in osteoclasts in the subchondral bone and cartilaginous endplate of the OVX group, consistent with the previous findings.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that IL‐17 induced synovial fibroblasts to release MMP‐1 and MMP‐3 in RA, facilitating tissue destruction . Osteoclasts were closely related to the degradation of osteoarthritic cartilage . With the involvement of M‐CSF and IL‐17, monocytes/macrophages could differentiate and fuse to osteoclasts in the bone or giant cells in the chronic inflammatory site in RA.…”
Section: The Function Of Th17 Cells On Ramentioning
confidence: 99%
“…These results confirm conservation of MMnet in humans and demonstrate associations between MMnet and osteoclast multinucleation and bone mass. Furthermore, the association of MMnet with osteoarthritis suggests involvement of osteoclasts in articularcartilage degradation, an area that is gaining increasing attention(Goldring and Goldring, 2016;Lofvall et al, 2018).To validate the function of MMnet in vivo, we first investigated the role of the hub gene, Bcat1, in knockout mice and demonstrated important new roles for BCAT1 in osteoclast formation and function, and the physiological maintenance of adult bone mass and strength.…”
mentioning
confidence: 99%